Creación de una marca de helados con licor como plan de negocios de una heladería en la ciudad de Machala. - Lopez Macas, Maria Belen (My University, 2018)
At the time the entrepreneurship project was developed, in the City of Machala with the idea of generating wealth as new sources of employment are established and the most important thing that is sought to adequately satisfy consumers, in this way allows to improve the quality of life of the inhabitants of the city generating employment, in addition to encouraging micro-business development and therefore reducing migration in the City of Machala. This entrepreneurial project addresses environmental problems with the purpose of contributing to the sustainable development of the City of Machala, interacting with the community, with the purpose of generating alternative solutions to the problems that impede social development, it is intended to carry out a project that contributes to generate value in organizations, to the diversification and reactivation of the economy that generates social welfare. Taking into consideration the: "CREATION OF A MARKET OF ICE CREAMS WITH LICOR AS A BUSINESS PLAN OF A ICE CREAM IN THE CITY OF MACHALA" It is important to consider the economic contribution that with the present investment project was made in the foreground to the suppliers of the raw material for the elaboration of "Ice cream liquor" since it will improve the current economy of the families. Just as it seeks to develop a product that is accessible to consumers in the City of Machala. The creation of new production units relates the product to the profile of the consumer by offering products with characteristics that adequately meet the needs of the consumer, with affordable prices without generating greater impact on their economy. It should be noted that liqueur ice cream has its own raw material proteins. The main objective was to conduct market research through a study of perceptions and preferences to establish the degree of acceptance of ice cream with liquor by applying the quantitative method with the instrument of the observation guide in the pre-sale process as well as the specific objectives, among them were the execution of the reception that the product had in the market segmentation where it was determined that 87.5% of tasters accept the product because the existing companies do not offer or offer this product, in the feasibility The qualitative method by point was used to determine the best location of the business, it is worth emphasizing that the company will be located in the City of Machala, specifically in the Las Brisas Citadel. In addition, a legal administrative study was designed where the most relevant points is the legal constitution of the company with which it is stated that the business name with which it will be registered will be "LIQ CREAM", which is registered as a small company because it will count with four employees, a financial study was conducted within which the different budgets were developed with real values of the local market, determining a total investment of $ 8,760 dollars, which consist of own capital in a 12.94% and the rest with a credit in the JEP Cooperative at an interest rate of 15.09. According to the financial indicators in the statement of profit and loss a profit of 5863.08 dollars is obtained. As a final part of this thesis work has been plated the respective conclusions and recommendations that have been reached during the development of the same, thus giving the necessary sequence to the project and especially showing the benefits that will be provided to society that is to meet their needs fully.
Al momento que se desarrolló el proyecto de emprendimiento, en la Ciudad de Machala con idea de generar riqueza ya que se establecen nuevas fuentes de empleo y lo más importante que se busca satisfacer de manera adecuada a los consumidores, de esta manera permite mejorar la calidad de vida de los habitantes de la ciudad generando empleo, además de que se incentiva el desarrollo micro- empresarial y por ende se reduce la migración en la Ciudad de Machala. El presente proyecto de emprendimiento aborda problemas del entorno con el propósito de coadyuvar al desarrollo sustentable de la Ciudad de Machala, interactuando con la comunidad, con la finalidad de generar alternativas de solución a los problemas que impiden el desarrollo social, se pretende realizar un proyecto que contribuya a generar valor en las organizaciones, a la diversificación y reactivación de la economía que genere bienestar social. Tomando en consideración la: “CREACIÓN DE UNA MARCA DE HELADOS CON LICOR COMO PLAN DE NEGOCIOS DE UNA HELADERÍA EN LA CIUDAD DE MACHALA”. Es importante considerar el aporte económico que con el presente proyecto de inversión se realizó en un primer plano a los proveedores de la materia prima para la elaboración de “Helados de licor” ya que se mejorará la economía actual de las familias. Al igual que se busca elaborar un producto que sea accesible para los consumidores de la Ciudad de Machala. La creación de nuevas unidades de producción relaciona el producto con el perfil del consumidor al ofrecer productos con características que satisfagan adecuadamente las necesidades del consumidor, con precios accesibles sin generar mayor impacto en su economía. Cabe recalcar que los helados de licor tienen proteínas propias de la materia prima. El objetivo principal fue realizar una investigación de mercado a través de un estudio de percepciones y preferencias para establecer el grado de aceptación de los helados con licor aplicando el método cuantitativo con el instrumento de la guía de observación en el proceso de la preventa así también los objetivos específicos, entre ellos fueron, la ejecución de la acogida que tuvo el producto en la segmentación de mercado donde se determinó que un 87,5% de degustadores aceptan el producto por que las empresas existentes no brindan ni ofrecen este producto, En la factibilidad técnica se ocupó el método cualitativo por punto para determinar la mejor ubicación del negocio, vale recalcar que la empresa estará situada en la Ciudad de Machala específicamente en la Ciudadela Las Brisas. Además se diseñó un estudio legal administrativo donde los puntos más relevantes es la constitución legal de la empresa con la cual se manifiesta que la razón social con la que será registrada la misma será “LIQ CREAM” , que se registra como una empresa pequeña porque contara con cuatro empleados, se realizó un estudio financiero dentro del cual se desarrolló los diferentes presupuestos con valores reales del mercado local, determinando una inversión total de $8,760 dólares, que constan con un capital propio en un 12,94% y el resto con un crédito en la Cooperativa JEP a una tasa de interés del 15,09. Según los indicadores financieros en el estado de pérdidas y ganancias se obtiene una utilidad de 5863,08 dólares. Como parte final del presente trabajo de tesis se ha plateado las respectivas conclusiones y recomendaciones que han sido alcanzadas durante el desarrollo del mismo, dando así la secuencia necesaria al proyecto y sobre todo mostrando los beneficios que se brindará a la sociedad que es satisfacer sus necesidades a cabalidad.
Keywords: EMPRENDIMIENTO; PROYECTO; PLAN DE NEGOCIO